2018
DOI: 10.1016/j.ccell.2017.11.009
|View full text |Cite|
|
Sign up to set email alerts
|

Dual Targeting of Oncogenic Activation and Inflammatory Signaling Increases Therapeutic Efficacy in Myeloproliferative Neoplasms

Abstract: Genetic and functional studies underscore the central role of JAK/STAT signaling in myeloproliferative neoplasms (MPNs). However, the mechanisms that mediate transformation in MPNs are not fully delineated, and clinically utilized JAK inhibitors have limited ability to reduce disease burden or reverse myelofibrosis. Here we show that MPN progenitor cells are characterized by marked alterations in gene regulation through differential enhancer utilization, and identify nuclear factor κB (NF-κB) signaling as a ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
156
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(164 citation statements)
references
References 69 publications
(77 reference statements)
6
156
2
Order By: Relevance
“…Corroborating with these findings are the promising early clinical activity of SMAC mimetic LCL-161 in MF (Pemmaraju et al, 2018) and pre-clinical data demonstrating TNF-induced apoptotic activity of birinapant (a bivalent IAP inhibitor) in MF cell lines at concentrations that selectively block cIAP, but not XIAP (Heaton et al, 2018). Elevated cIAP and downregulation of the pro-apoptotic MAPK8 through the aberrantly activated TNF-TNFR2 autocrine loop promotes NF-kB activation, which favours survival and promotes further inflammatory cytokine production (Hoesel & Schmid, 2013;Kleppe et al, 2018). The exact mechanism underlying the aberrant modulation of TNF-TNFR2 signalling in JAK2 V617F is an area of active investigation.…”
Section: Role Of Iaps and Tumour Necrosis Factor (Tnfa) In Myelofibrosismentioning
confidence: 82%
“…Corroborating with these findings are the promising early clinical activity of SMAC mimetic LCL-161 in MF (Pemmaraju et al, 2018) and pre-clinical data demonstrating TNF-induced apoptotic activity of birinapant (a bivalent IAP inhibitor) in MF cell lines at concentrations that selectively block cIAP, but not XIAP (Heaton et al, 2018). Elevated cIAP and downregulation of the pro-apoptotic MAPK8 through the aberrantly activated TNF-TNFR2 autocrine loop promotes NF-kB activation, which favours survival and promotes further inflammatory cytokine production (Hoesel & Schmid, 2013;Kleppe et al, 2018). The exact mechanism underlying the aberrant modulation of TNF-TNFR2 signalling in JAK2 V617F is an area of active investigation.…”
Section: Role Of Iaps and Tumour Necrosis Factor (Tnfa) In Myelofibrosismentioning
confidence: 82%
“…Inflammation plays a role in all MPN subgroups, most pronounced in MF patients. It has been shown that inhibiting specific cytokines like IL-1β or the NfkB pathway can either decrease hematopoietic cell growth ex vivo ( 61 ) or even diminish fibrosis in vivo ( 62 ). Targeting soluble mediators in MF patients serves predominantly to ameliorate constitutional symptoms and reduce frequent comorbidities like MF -associated anemia.…”
Section: Therapeutic Targeting Of Soluble Mediators the Malignant Bomentioning
confidence: 99%
“…The NfκB pathway has been shown to be activated in JAK2 mutated MPN. Recently, a potential combinatorial therapeutic approach for MPN patients has been proposed, by targeting inflammation through reduction of NfκB activity using BET inhibition in combination with JAK inhibition ( 62 ). Using MPN mouse models, Kleppe et al showed that increased NfκB activity in MPN is partly cell-extrinsic, highlighting the importance of targeting the BM microenvironment.…”
Section: Therapeutic Targeting Of Soluble Mediators the Malignant Bomentioning
confidence: 99%
See 1 more Smart Citation
“…All MPNs are characterized by chronic inflammatory state (reviewed in [7][8][9]). Thus, oncogenic and inflammatory signaling, both known to fuel genotoxic stress and tumorigenesis in the hematopoietic system in a cell-autonomous and non-cell-autonomous manner, converge in disease evolution of MPNs [10][11][12][13][14]. Therefore, CML and PV provide an excellent model of inflammation-associated neoplasia for investigating mechanisms of DNA damage accumulation and DNA damage response (DDR) activation throughout early pre-cancerous ontogeny.…”
Section: Introductionmentioning
confidence: 99%